Computing the Minkowski sum of prisms - Diethard Pallaschke; Joachim Rosenmüller (Bielefeld University, Institute of Mathematical Economics (IMW), 2005)
Within this paper we study the Minkowski sum of prisms ('Cephoids') in a finite dimensional vector space. We provide a representation of a finite sum of prisms in terms of inequalities.
urn:nbn:de:hbz:361-6466
Keywords: 330; Convex analysis; Minkowski sum; polytopes